Cerclage sling technique using temporalis muscle fascia to manage paralytic lagophthalmos: A preliminary study - Barros, V. P.O. [UNESP]; Chaves, I. L.C. [UNESP]; Meneghim, R. L.F.S. [UNESP]; Padovani, C. R. [UNESP]; Schellini, S. A. [UNESP] (Elsevier, 2024)
Purpose: Despite various existing surgical techniques, treatment of facial nerve palsy remains difficult. The purpose of this report is to present the cerclage sling technique using temporalis fascia to manage paralytic lagophthalmos. Methods: A series of six patients underwent a cerclage sling technique using temporalis muscle fascia to treat paralytic lagophthalmos. The technique is presented in detail. Symptoms, palpebral fissures, and lagophthalmos were assessed pre- and postoperatively. Data were submitted for statistical analysis. Results: After surgery, all patients achieved a reduction in clinical symptoms. The upper eyelids had lowered, and the inferior eyelids had elevated, reducing ocular exposure even if mild residual lagophthalmos was present. Conclusion: Cerclage using the temporalis muscle fascia sling technique is a safe and effective procedure to treat facial nerve paralytic lagophthalmos. A reduction in ocular exposure and lagophthalmos provides improvement in clinical symptoms and eyelid function.
Technique de sanglage avec le fascia du muscle temporal pour traiter la lagophtalmie paralytique : une étude préliminaire
Keywords: Cerclage; Paralytic lagophthalmos; Sling technique; Temporal muscle fascia